A high-performance 10 mm diameter MEMS fast steering mirror with integrated piezoresistive angle sensors for laser inter-satellite links - Wenli Xue; Yichen Liu; Xingwang Zhu; Mingkun Wang; Zhichao Weng; Yongquan Su; Yi Yang; Hongfeng Zhao; Yang Wang; Hao Chen; Lihao Wang; Zhenyu Wu (Microsystems & Nanoengineering)
Abstract This paper presents a compact and high-performance piezoelectric micro-electro-mechanical system (MEMS) fast steering mirror (FSM) designed for use in laser inter-satellite links (ISLs). The FSM features a large optical aperture of 10 mm and is batch fabricated using an 8-inch wafer-level eutectic bonding process, packaged into a volume of 26 × 22 × 3 mm3. Notably, the piezoresistive (PZR) sensor is integrated on the spring of the FSM to facilitate precise beam control. Furthermore, an intermediate directional defect structure is novelly designed to create a Stress Concentration Region (SCR), effectively improving PZR sensitivity from 3.3 mV/(V∙mrad) to 5.4 mV/(V∙mrad). In this article, various performance metrics of the FSM are tested, including the mechanical characteristics, PZR sensor properties, and mirror optical quality, which all meet the requirements for laser ISLs. Results indicate that the FSM achieves a high resonant frequency (>1 kHz) and a low nonlinearity of 0.05%@ ± 2.1 mrad. A remarkable minimum angular resolution of 0.3 μrad and a repeated positioning accuracy of 1.11 μrad ensure exceptional pointing precision. The open-loop control is driven by the double-step algorithm, resulting in a step response time of 0.41 ms and achieving a control bandwidth over 2 kHz. Additionally, the integrated angular sensor demonstrates a nonlinearity of 0.09%@ ± 1.05 mrad, a sensitivity of 5.1 mV/(V∙mrad), and a minimum angular resolution of 0.3 μrad. Under quasi-static driven conditions (500 Hz @ ± 2 mrad), the maximum dynamic deformation of the mirror surface is merely 2 nm.